Calculation of multivariate normal probabilities by simulation, with applications to maximum simulated likelihood estimation - Lorenzo Cappellari; Stephen P. Jenkins (Institute for the Study of Labor (IZA), 2006)
We discuss methods for calculating multivariate normal probabilities by simulation and two new Stata programs for this purpose: -mdraws- for deriving draws from the standard uniform density using either Halton or pseudo-random sequences, and an egen function -mvnp()- for calculating the probabilities themselves. Several illustrations show how the programs may be used for maximum simulated likelihood estimation.
Keywords: C15; C51; C87; 330; simulation estimation; maximum simulated likelihood; multivariate probit; Halton sequences; pseudo-random sequences; multivariate normal; GHK simulator